RETRACTED: Rhodomyrtus tomentosa (Aiton) Hassk. (haramonting) protects against allethrin-exposed pulmo damage in rats: mechanistic interleukins - Situmorang, Putri Cahaya; Ilyas, Syafruddin; Syahputra, Rony Abdi; Nugraha, Alexander Patera; Putri, Mimmy Sari Syah; Rumahorbo, Cheryl Grace Pratiwi (Frontiers in Pharmacology, 2024)
Inhaling Allethrin (C19H26O3) may induce oxidative stress in lung cells by causing the formation of free radi-cals. Interleukins (IL) are a group of secreted cytokines or proteins and signaling molecules initially produced as an immune response by leukocytes. Rhodomyrtus tomentosa (Aiton) Hassk. (haramonting) contains antioxidants that may prevent lung damage induced by allethrin-containing electric mosquito repellents. In this study, six groups of rats were exposed to allethrin via an electric mosquito repellent, including positive, negative, and comparison control groups and three groups were administered Rhodomyrtus tomentosa (Aiton) Hassk at 100 mg/kg BW, 200 mg/kg BW, and 300 mg/kg BW. After thirty days, the pulmonary tissue and the blood were taken for immunohisto-chemical and ELISA analysis. The accumulation of inflammatory cells causes the thickening of the alveolar wall structures. Injuries were more prevalent in the A+ group than in the other groups. The connection between the alveoli and blood capillaries, which can interfere with alveolar gas exchange, is not regulated, and the lu-minal morphology is aberrant, causing damage to the alveolar epithelial cells. Exposure to electric mosquito coils containing allethrin can increase the expression of interleukin-1, interleukin-8, interleukin-9, and interleu-kin-18 in blood serum and tissues while decreasing the expression of interleukin-6 and interleukin-10. Like the Vitamin C group, Rhodomyrtus tomentosa can increase alveolar histological alterations by decreasing the ex-pression of IL-1 , IL-8, IL-9, and IL-18 while increasing IL-6 and IL-10. So that this plant can be developed in the future as a drug to prevent lung harm from exposure.